Practical applications of cardiovascular magnetic resonance. Issue 1 (5th July 2010) - Alpendurada, F; Wong, J; Pennell, D J
Abstract : Recent developments in magnetic resonance imaging have focused attention on evaluation of patients with cardiac disease. These improvements have been substantiated by a large and expanding body of clinical evidence, making cardiovascular magnetic resonance the imaging modality of choice in a wide variety of cardiovascular disorders. A brief review on the current applications of cardiovascular magnetic resonance is provided, with reference to some of the most relevant studies, statements and reviews published in this field.